The second sex - Beauvoir, Simone de, 1908-1986 (Vintage, 2011)
Newly translated and unabridged in English for the first time, Simone de Beauvoir's masterwork is a powerful analysis of the Western notion of "woman," and a groundbreaking exploration of inequality and otherness. This long-awaited new edition reinstates significant portions of the original French text that were cut in the first English translation. Vital and groundbreaking, Beauvoir's pioneering and impressive text remains as pertinent today as it was sixty years ago, and will continue to provoke and inspire generations of men and women to come.